The impact of Digital literacy on ICT self-efficacy in Islamic secondary school teachers in District Kot addu South Pakistan - Chaudhary, Muhammad Kashif Majeed; Tunku Badariah Binti Tunku Ahmad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Digital literacy is the skill of using digital technologies in order to find, assess and produce relevant information and products. ICT self-efficacy refers to self-confidence in instructional use of Information and Communication Technology tools.This paper focuses on effects of Digital Literacy on ICT self-efficacy of teachers in Islamic secondary schools in District Kot Addu South Pakistan. Hence, probing into how digital literacy affects teacher’s self efficacy when using ICT in teaching becomes relevant given rising push on adoption of technology in learning. The results are expected to contribute to the body of knowledge regarding professional development needed to support appropriate incorporation of technology into teaching practices.It seeks to alert professional development providers on the potential of impacting teacher confidence and competence on using technological tools in instruction.This paper presents a qualitative investigation concerned with the effects of digital literacy on ICT self-efficacies of teachers in the Islamic secondary schools in District Kot Addu, South Pakistan. The research sought to establish the present level of use of, and confidence in use of, information communication technology among teachers; personal computer/Internet literacy skills; and correlation between these skills and attitude towards the use of ICT in teaching. In this study, data was collected through use of semi structured interviews and focus group discussions with fifteen teachers from five Islamic secondary schools. Finally, through analyzing themes identified in the cross-case analysis, it was shown that although most teachers adopted digital literacy and were comfortable with technological tools, they lacked adequate knowledge on how to incorporate digital technologies with higher complexity into their teaching practice. In addition, the study showed that the profile of digital literacy influenced ICT self efficacy, the need to address with immediacy and desire the continuing professional learning to improve on it. The study has therefore called for enhanced training that not only increases computer literacy skills but also the level of self-confidence in the use of ICT in teaching to enhance teaching practices in era of technology.The professional development programs should then focus on developing the skills that would increase ICT self efficacy among teachers so as to increase the level of self confidence in integration of technology in teaching and learning practices.